Interface between mental health and the COVID-19 pandemic: the perspective of health professionals (Research, Society and Development, 2021)
Mental health has currently been marked by several reformulations, including the intensification of the health medicalization and the new coronavirus pandemic. This work aimed to describe the perception of mental health by professionals of residency programs in health, in 2020, during the COVID-19 pandemic. It’s an observational and transversal study, with a quantitative approach. We have done a structured, self-applied and online questionnaire, for 52 residents of the Uni and Multi Professional Residency Programs at the Universitary Hospital of the Federal University of Juiz de Fora. The obtained data were processed using as analysis method descriptive statistics and the chi-square test to verify the association between self-perception of mental health, sociodemographic variables and professional profile. In order to verify the effect of mental health care, logistic regression analysis was performed. The results showed a significant worsening in the perception of physical and mental health by residents, comparing the period before and during the pandemic in 2020, and that the previous and continuous mental health care was a protective factor for physiological changes perceived by residents in the period. Thus, psychosocial support to health professionals is essential, especially when we consider the pandemic scenario.